A Global Nearest-Neighbour Depth Estimation-based Automatic 2D-to-3D Image and Video Conversion - Anusha M Sidhanti; Jyothsna Madam; Mounesh V M (Institute of Advanced Engineering and Science, 2014)
The proposed work is to present a new method based on the radically different approach of learning the 2D-to-3D conversion from examples. It is based on lobally estimating the entire depth map of a query image directly from a repository of 3D images (image depth pairs or stereo pairs) using a nearest-neighbour regression type idea.